Web application for large-scale multidimensional data visualization - Dzemyda, Gintautas; Marcinkevičius, Virginijus; Medvedev, Viktor (Mathematical Modelling and Analysis, 2011)
In this paper, we present an approach of the web application (as a service) for data mining oriented to the multidimensional data visualization. This paper focuses on visualization methods as a tool for the visual presentation of large-scale multidimensional data sets. The proposed implementation of such a web application obtains a multidimensional data set and as a result produces a visualization of this data set. It also supports different configuration parameters of the data mining methods used. Parallel computation has been used in the proposed implementation to run the algorithms simultaneously on different computers.